THE MOST COMMON OVERUSE INJURIES OF THE FINGERS IN SPORT CLIMBERS – CURRENT DIAGNOSTIC AND TREATMENT STRATEGIES - Kowal , Adam; Majda, Antoni; Sitko , Natalia; Makowska , Paulina; Gontarczyk, Joanna; Laske, Alicja; Sowa, Martyna; Pająk, Julia; Kucharski , Kacper; Kamosińska, Anna; Sokołowska, Julia; Dawidowicz, Marcel (International Journal of Innovative Technologies in Social Science, 2026)
In recent years, we have observed a rapid increase in the popularity of sport climbing, which is associated with an increased number of finger injuries, particularly among beginners and intermediate climbers. The aim of our study was to present the most common finger injuries in climbers, the mechanisms by which they occur, diagnostic methods, and treatment approaches based on available scientific research.We focused on three main finger injuries: finger flexor tendon pulleys , inflammation of tendons and synovial sheaths, and phalangeal epiphyseal fractures.  We highlighted the mechanisms of injury, particularly in the context of using the “full crimp” grip, which significantly increases the load on the fingers.Indications for conservative and surgical treatment, characteristic clinical symptoms, and the diagnostic significance of ultrasound and magnetic resonance imaging in pulley injuries were presented. In the case of tendonitis, we highlighted the role of training overload and the effectiveness of conservative treatment. In the context of phalangeal injuries, we highlighted their frequent occurrence in young athletes, appropriate diagnosis, and long-term rehabilitation.  Finger injuries in climbers are a serious problem, the incidence of which is increasing along with the popularity of this sport. Early diagnosis and proper identification are key to a quick return to sport climbing.Methodology: This study provides an overview of the available scientific research describing the most common finger injuries among sport climbers. In our review, we focused on the mechanisms underlying these injuries, their diagnosis, and possible treatment options.In our search for available scientific studies, we useed the following databases: PubMed, Scopus and Google Scholar, covering the period 1989–2021. When searching for available clinical studies, we focused on:• types of injuries (ligament damage, tendinitis and tenosynovitis, phalangeal head fractures)• mechanisms of injury, with particular emphasis on the ‘full crimp’ grip• diagnostic methods (ultrasound, magnetic resonance imaging, X-ray)• treatment strategies (conservative and surgical).